Developing foreign students’ self-education competence in the course of learning the Ukrainian language - Rotova, N. (Problems of Engineer-Pedagogical Education, 2021)
The article describes the significance of self-education in vocational lifelong learning, in which the person him/herself can only act as the main subject of planning, organization, and regulation of education, and the process of acquiring education turns into the process of self-education. The author indicates that the vast majority of students of higher education establishments are not ready and cannot effectively organize the process of their self-education. Today, independent work of students is one of the main components in the overall structure of the educational process in general and in case of foreign students in particular. It is emphasized that the importance of this question is also related to the new role of independent work, which it acquires in connection with the transition to the competent paradigm of education, as well as in regard to the need to adapt to full-fledged training in a pandemic. In addition, the specificity of the foreign language is that the language cannot be taught, the language can only be learned, i.e. the student must manifest the maximum activity and independence in all types of speech activities. The author determines that, in general, the quality of assimilation of educational material, in particular self-education, directly depends on the implementation of several simple rules by students – multiple, systematic and purposeful processing of educational material ensures its reliable fixation in the long-term memory. It is emphasized that self-education competence is one of the most relevant competences that should be formed in students in the educational process of higher education institutions. Independent work allows expanding the worldview by means of assimilating linguistic and country studies information, changing the attitude towards the language studied in a positive direction, as well as shaping students’ understanding of the necessity to study not only at higher education institutions, but also throughout life. Particular emphasis in the process of foreign students’ independent work is placed on the development of motivation and interest in learning the Ukrainian language as well as specialized disciplines, since these very qualities form the internal outcomes of students’ educational activity. Self-education competence is formed on the basis of the experience of independent attempts and achievements in self-education activity, the development of one’s own individual training system, a gradual transition from copying self-education samples to creating one’s own self-education model, the inclusion of self-education in the lifestyle of students.